Development and sensory analysis of shampoo for curly hair - Rigon, Roberta B. [UNESP]; Souza, Rafael R.; Souza, Rebeca C.; Bighetti, Aparecida E.; Chorilli, Marlus [UNESP] (My University, 2013)
Objective: This study aimed to compare the sensory performance of a shampoo formulation with Polyurethane-14, AMP-acrylates copolymer (PAAC) in relation to control formulation in curly and natural hair tresses. Methods: Curly and natural hair tresses (n = 8) of equal size and weight were pre-treated by washing with a standard shampoo. After the hair tresses were treated with a formulation containing polymer (formulation A) and compared to hair tresses treated with control formulation (Formulation B). Each panelist (n=2) is asked to indicate which tress performs better for each of seven sensory attributes evaluated (quantity and creamy foam, combing, wet touch, frizz formation, curl definition and volume). It was collected images of hair tresses at 0, 1, 2, 4 and 24 hours of washing, comparing the attributes: volume, frizz formation and curl definition. The results were analyzed using table to test of paired assessment, being: SUPERIOR results - 8 and 7 positive evaluations; SIMILAR results - 2 to 6 positive evaluations; INFERIOR results - 1 and 0 positive evaluations. Results: The addition of the PAAC on the shampoo formulation provided definition and modeling of curls, reducing volume and frizz in 24 hours. There was also lower foam formation in the formulation with polymer PAAC. However, it is important to note that this attribute has inversely proportional effect to the creamy foam, since more creamy foam, smaller quantity. Conclusions: It was concluded that the shampoo developed was effective in defining and modeling curl in natural and curly hair.
Keywords: AMP-acrylates copolymer; Curly hair; Polyurethane-14; Sensory analysis; Shampoo; copolymer; polyurethane 14 AMP acrylate copolymer; shampoo; unclassified drug; controlled study; foam; hair analysis; hair growth; hair texture; scalp hair; sensory analysis